Justification for the need to conduct research on the formation of general competencies of future officers in the process of professional training in the national guard of Ukraine - Medvid, Mykhailo; Havryshchuk, Mykhailo (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The war has changed the environment of the service and combat activities of the officers in the National Guard of Ukraine. Today, military units perform functions of the National Guard of Ukraine that are atypical for peacetime, including participation in the implementation of the legal regime of martial law and involvement in territorial defense tasks. The new conditions of this environment include: an increase in the average age of subordinate personnel, which often exceeds the age of graduates from higher military educational institutions; the necessity to make quick decisions in conditions of uncertainty; increased responsibility for the lives and health of subordinate personnel, and more. This study was conducted to test the hypothesis of the impact of new conditions in the service and combat environment on the satisfaction of graduates from higher military educational institutions of the National Guard of Ukraine with the general competencies they have acquired. The object of the research is the results of the service and combat activities of units in the National Guard of Ukraine, which depend on the competencies of their leaders. The following research methods were used to test the hypothesis: survey, analysis, and synthesis. The survey of graduates from higher military educational institutions of the National Guard of Ukraine was conducted remotely using questionnaires created in Google Forms in April-May 2023. According to the survey results, it was found that less than one-third of the graduates are satisfied with their acquired Soft Skills, which significantly differs from similar surveys conducted during their assessment in the higher military educational institution. The analyzed survey results confirmed the hypothesis, and its synthesis resulted in the formulation of proposals for further research dedicated to determining the pedagogical conditions for the formation of general competencies of future officers in the National Guard of Ukraine in the process of professional training.